2021
DOI: 10.32725/kont.2020.035
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for teachers in the context of postgraduate nursing education: Polish experiences

Abstract: The competency of nurse teachers and collaboration between nurse educators, nurse leaders and mentors are crucial for achieving highquality Evidence-Based nursing education. The profession of a nurse teacher is one of public trust and it requires the integration of skills, attitudes, standards, and theoretical knowledge as well as awareness of individual, organisational and social circumstances. The data were collected via email using a structured questionnaire (A Tool for the Evaluation of Requirements of a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Factors influencing the occurrence of delirium in the period from admission to hospital until complete recovery should be sought [ 33 , 34 ]. The study by Ozga et al showed that nurses face a multitude of limitations due to procedures, lack of equipment, and personnel issues [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors influencing the occurrence of delirium in the period from admission to hospital until complete recovery should be sought [ 33 , 34 ]. The study by Ozga et al showed that nurses face a multitude of limitations due to procedures, lack of equipment, and personnel issues [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further education of nurses and other medical groups in detecting and dealing with delirium is necessary. The competency of nurse teachers and collaboration between nurse educators, nurse leaders, and mentors are crucial for achieving high quality evidence-based nursing education [32,35].…”
Section: Implications For Practicementioning
confidence: 99%
“…Nurse educators tend to evaluate their competences higher than other evaluators. In comparison, in studies that seek to study students' and educators' evaluations, the nurse educators' self-evaluations are more positive than the evaluations given to them by their students (Mikkonen et al, 2018;Ozga et al, 2021;Salminen et al, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The ERNT instrument was selected because it has been widely used and has performed well due to its general nature (Ozga et al, 2021;Salminen et al, 2013Salminen et al, , 2021. Additionally, its face validity and internal consistency were tested in previous study, where…”
Section: The Instrumentmentioning
confidence: 99%
See 1 more Smart Citation